Agreement on Core Components of an E-Learning Cultural Competence Program for Public Health Workers in South Korea: A Delphi Study - Duckhee Chae; Hyunlye Kim; Jae Yong Yoo; Jina Lee (Elsevier, 2019)
Summary: Purpose: This study aimed to seek agreement on the core components of an e-learning cultural competence program for Korean public health workers (PHWs) while prioritizing educational content areas. Methods: A two-round Delphi study was performed with 16 Korean experts from five disciplines. Data were collected between August 30 and November 24, 2017. A questionnaire was developed from literature reviews and previous focus group interviews concerning PHWs. The panel members were asked to rate the importance and urgency of educational content areas and the effectiveness of teaching-learning methods and gave opinions on their appropriate frequency, duration, and target audience. Responses were analyzed using descriptive statistics. A median of 4.0 or greater or a rate of agreement of 75% or greater was considered a "consensus" for the purposes of this study. Results: All consenting participants responded to two-round surveys. Participants reached consensus on thirty-one educational content areas. Of these, the highest priorities were "necessity of cultural competence of PHWs," "health characteristics according to race and ethnicity," and "establishing trusting relationships with migrants." The most effective teaching-learning method was case-based learning, with seven to eight sessions of training and duration of fewer than 30 minutes per session. Conclusion: Multidisciplinary experts proposed 12 prioritized educational content areas and effective teaching-learning methods as well as their frequency, duration, and target audiences, reflecting Korea-specific multicultural phenomena and the nature of the work of PHWs. These findings can contribute to preparing PHWs to provide culturally competent services to migrants in their communities. Keywords: cultural competency, delphi technique, education, health personnel, public health